1972
DOI: 10.2337/diab.21.2.s538
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion Mechanisms and Glucose Metabolism in Isolated Islets

Abstract: The in vitro effects of glucose and analogs of glucose on insulin secretion have been reinvestigated with rat and mouse islets. Curves relating rates of insulin secretion to glucose concentration were sigmoid with a K m of 6-8 mM and tending to V max at approximately 20 mM glucose. Mannose and glucosamine were the only analogs of glucose which stimulated secretion in the absence of glucose. Fructose, N-acetyl glucosamine and galactose (rat only) potentiated secretion at 2.5 or 5 mM glucose but not at 20mM gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
57
2

Year Published

1975
1975
2007
2007

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(73 citation statements)
references
References 8 publications
14
57
2
Order By: Relevance
“…At higher levels, no stimulatory effect is observed as has already been reported [3] (fig.1). Fig.1.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…At higher levels, no stimulatory effect is observed as has already been reported [3] (fig.1). Fig.1.…”
Section: Resultssupporting
confidence: 79%
“…It is presumed to act by binding to the glucose receptor cells in the ventromedical hypothalamus. To date there has been little reported on the direct effects of gold thioglucose on isolated islets of Langerhans, though in [3] it was suggested that, at high concentrations it may have no effect on islet function.…”
Section: Introductionmentioning
confidence: 99%
“…A striking correlation between the rates of insulin release and glucose metabolism in non-cultured islets has previously been shown [20,21,22]. After culture of islets in the presence of high or low glucose concentrations, Andersson [2] found increased rates of glucose oxidation in the high-glucose cultured islets, an observation which provides an additional explanation of the greater insulin-releasing effect of glucose in these islets.…”
Section: Discussionmentioning
confidence: 82%
“…The correlation between 45Ca 2+ uptake and insulin release was not as strict as previously reported for rat islets [14, !5]. Thus, tolbutamide, mannose, and L-leucine are clearly less potent than D-glucose in stimulating the release of insulin from normal mouse islets [ 1,2] as well as from the islets of ob/ob-mice [13]. However, these insulin secretagogues appeared equally effective in stimulating the lanthanum-nondisplaceable 45Ca2+ uptake.…”
Section: Discussionmentioning
confidence: 99%